2020
DOI: 10.1002/pssr.202000501
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Photocurrent and Fast‐Response Polarity‐Controlled ZnO‐Based UV Photodetector Grown by a Sol–Gel Process

Abstract: Oxygen‐polar (O‐polar) and nonpolar ZnO‐based UV photodetectors (PDs) are fabricated using a sol–gel (SG) method on polarity‐controlled ZnO seed layers grown by atomic layer deposition (ALD). O‐polar c‐plane and nonpolar a‐plane ZnO films grown using the SG process are obtained using ALD‐grown ZnO seed layers on c‐plane and r‐plane sapphire substrates, respectively. In addition, the photoluminescence intensity of the O‐polar c‐plane ZnO film is higher than that of the nonpolar a‐plane ZnO film owing to the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…It is believed that the decrease in photocurrent above 80 °C is due to thermal oxidation becoming dominant above this temperature. [ 18 ] The thermal oxidation process is thought to accelerate the desorption of surface oxygen, which negatively affects the photocurrent reduction of ZnO PD. Figure 5b illustrates the relationship between the saturation time for the maximum photocurrent of the ZnO PD and the reciprocal temperature of the SWCNT film heater.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is believed that the decrease in photocurrent above 80 °C is due to thermal oxidation becoming dominant above this temperature. [ 18 ] The thermal oxidation process is thought to accelerate the desorption of surface oxygen, which negatively affects the photocurrent reduction of ZnO PD. Figure 5b illustrates the relationship between the saturation time for the maximum photocurrent of the ZnO PD and the reciprocal temperature of the SWCNT film heater.…”
Section: Resultsmentioning
confidence: 99%
“…Using Arrhenius equation, the activation energy for the photocurrent saturation time of ZnO PDs is calculated to be 203 meV, which is lower than values obtained from conventional temperaturedependent measurement system. [18,46] It implies that the hybrid ZnO PDs with SWCNT film heater are more efficient in adding thermal energy to improve photocurrent, compared to conventional separated thermal heating system. Figure 5c shows the rise and recovery times of the hybrid ZnO PDs as a function of the operating temperature of the SWCNT film heater, which is controlled by applying a voltage for 0-40 V. The photoresponse rise time is defined as the time required to increase the photocurrent from 10% to 90% of the peak intensity, while the photo-recovery time is achieved by measuring the time required to decrease the photocurrent from 90% to 10% of its peak value.…”
Section: Time and Heating Temperature-dependent Photocurrent Of Hybri...mentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the results of other research groups shown in Table 1, it is found that the ZnO PDs prebaked at 150 °C had relatively good response times. [35][36][37][38][39] It is believed that this is because the adsorption and desorption reactions of oxygen on the ZnO surface occur most rapidly in PDs with the largest NWNs structure, leading to the fastest response times. [40,41] At 150 °C, the PDs exhibit the largest and most well-defined NWNs structure, which enhances the light absorption and extraction efficiency and leads to the fastest response times.…”
Section: Prebake Temperature-dependent Photocurrent Of Zno-based Uv Pdsmentioning
confidence: 99%